Rice-soy curls plant design - Contreras, Frederick R.; Martinez, Jayson T.; Ong, Mark Christopher E.; Temones, Daxter J. (College of Engineering, 1997)
Product: Rice-soy curls -- Plant capacity/day: 1,238 kg/day (41,267 bags @ 30g each) -- No. of operating days/year: 300 -- Source of technology: Food and Nutrition Research Institute, Dept. of Science and Tech. -- Target market: Distribution region/area - NCR, Income brackets - A, B, C income brackets -- Fixed capital investment: Php 10,083,960 -- Working capital: Php 4,719,912 -- Pre-operating expenses: Php 250,000 -- Financing scheme: 50% loan, 50% equity -- Interest rate (loan): 17% per annum -- Terms of payment: 5 years (amortized) -- Payback period: 1.67 years or 20.04 months -- Return on investment (ROI): 32.35% -- Break-even capacity/day: 1,015 kg/day (33,838 bags @ 30g each) -- Break-even selling price: Php 95.00/kg of product -- Proposed selling price: Php 100.00/kg of product